Discrete-event simulation input process modeling - Leemis, Lawrence M. (1996 Winter Simulation Conference Proceedings, 1996)
General guidelines for selecting probabilistic input models as part of a discrete-event simulation study are presented. Two short examples illustrating input modeling decisions are also presented, as opposed to a complete treatment of the subject.